(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study investigated the effects of dietary piperine (PIP) supplementation on feed efficiency, growth performance, digestive enzyme activity, hemolymph biochemistry, antioxidant and immune responses, and disease resistance in whiteleg shrimp (Litopenaeus vannamei) challenged with Vibrio parahemolyticus. Materials and Methods: A total of 320 shrimps (4.38 gm ± 0.2 gm) were randomly distributed into four treatments and fed a basal diet or supplemented with 0, 0.5 (PIP0.5), 1 (PIP1.0), and 2 (PIP2) gm/kg of diet. Results: The dietary inclusion of PIP significantly improved growth performance, blood proteins, and efficiency, resulting in the best results in the PIP2 group. Diets containing PIP led to significant improvements in crude protein and lipid content while also significantly reducing moisture content in a quadratic-dependent manner (p < 0.05). Shrimp in the PIP1 and PIP2 groups exhibited higher total protein and albumin levels compared to the free-PIP and PIP0.5 groups (p < 0.05). Shrimp-fed PIP-enriched diets showed lower lipid profiles (total cholesterol, triglycerides, and low-density lipoprotein) and liver enzymes (gamma-glutamyl transferase and lactate dehydrogenase) in a quadratic trend (p < 0.05) compared to the control diet. Shrimp-fed diets containing PIPs exhibited a significant quadratic increase in digestive enzyme activity compared to those without PIPs (p < 0.05). The inclusion of PIP in the diet significantly enhanced antioxidant enzymes and reduced malondialdehyde levels, as well as the inflammatory response (Interleukin 4, Interferon-gamma, and LYZ) in shrimp. Conclusion: These findings suggest that dietary PIP supplementation holds promise as a feed additive for enhancing growth, immunity, and disease resistance in whiteleg shrimp. J. Adv. Vet. Anim. Res., 11(4): 996–1006, December 2024 http://doi.org/10.5455/javar.2024.k850